A Grid-Tied SPV Array and BES Based Microgrid Control for Reduced Amplitude-Phase-Frequency Loop Coupling Effects and Disturbance Crosstalks - Chakraborty, Subhadip; Singh, Bhim; Modi, Gaurav; Panigrahi, Bijaya Ketan (IEEE transactions on industry applications, 2025)
The existence of a phase-locked loop (PLL) estimated voltage amplitude-frequency-phase angle coupling phenomenon poses a significant challenge in control of grid-tied renewable energy systems. Since inverter control of these systems necessitates accurate grid voltage information for grid-following mode (GFL) control, disturbances in any of these voltage parameters can propagate to others, causing fictitious disturbances and false estimations by PLL. These inaccurate estimations, along with spurious transients and overshoots, can lead to failures in inverter control or triggering of false control signals. To address these issues and enhance transient performance, this work introduces a multilayered reduced-order generalized integrator with an improved novel PLL (MROGI-IPLL) control structure for disturbance rejection immunity with reduced estimation loop crosstalk, thereby improving overall system power quality and control efficacy. Proposed control not only mitigates impact of voltage-side disturbances on system control but also reduces reflection of load harmonics, negative sequence, and reactive current components on grid side, in compliance with the IEEE std. 1547 power quality specifications. Unique advantages of proposed control algorithm are validated through simulation and experimental results in various test cases.